On the Translation of Otherness: The Univocal Case of Will Grayson, Will Grayson - Badenes, Guillermo (TTR, 2019)
Over the past twenty years, after the LGBT+ liberationist movement has managed to make new voices heard and had certain social gains, partly overturning decades of exclusion and segregation, gay literature has often focused on the stories of young men and women as a form of instilling positive values upon the future generations. The mainstream publishing world in Spanish has sometimes lagged behind LGBT+ times, publishing little queer literature and favoring mainly canonical authors. Translation criticism from the cultural margins raises questions regarding the voices of alterity and, in this respect, it highlights the visibility of translators (and publishing houses) as subjective factors in the translation process. The ideological analysis of literary translation may identify the role of translators as intercultural mediators who use strategies that accentuate or subdue the LGBT+ character of the texts they translate. The young-adult, gay novel Will Grayson, Will Grayson, written by John Green and David Levithan, presents an interesting challenge from the point of view of the separate discursive identities at play in it. Nonetheless, the novel was solely translated by Noemí Sobregués, a situation calling for closer analysis to revise the strategies used to represent the duality of the text in terms of idiolectal authorship. Using the tools provided by Keith Harvey (2000), this paper focuses on the analysis of the role of this translator in the rendition of the novel in Spanish, in the larger context of what it is that publishing houses seek when they publish LGBT+ literature: either to portray watered-down versions palatable to mainstream readerships, or to queerify their publishing catalogues, and thence, possibly, the canon at large.